Individual niche trajectories drive fitness variation. (10th July 2019) - Costa‐Pereira, Raul; Toscano, Benjamin; Souza, Franco L.; Ingram, Travis; Araújo, Márcio S.
Abstract: Variation in fitness across individuals is central to population growth, species coexistence and evolution by natural selection. Fitness variation associated with resource use is hugely consequential, but how this variation is generated and maintained within natural populations remains unclear. In particular, individual fitness may depend on many cumulative foraging decisions over time, but this hypothesis remains untested. We used multi‐tissue stable isotope analysis to determine isotopic niche trajectories within species, populations and sexes of thin‐toed frogs and explored how this temporal dimension of diet affects individual reproductive investment, body condition and parasite load. We found that individual frogs shifted their diets less than expected under a null model, likely due to functional trade‐offs that limit the incorporation of new prey types over time. However, within the observed range of diet shifts, individuals that modified their diet to a greater degree exhibited higher fitness, although this effect was sex‐dependent. We suggest that these different relationships between isotopic niche trajectory length and fitness within thin‐toed frogs are driven by variability in the resource environment, negative density dependence and allometric constraints. These strong fitness effects suggest that the temporal dimension of diet change is a potential target of natural selection and, therefore, could drive correlated evolution in phenotypic traits underlying diet flexibility. Our findings add a new level of complexity to the understanding of ecological and evolutionary consequences of niche variation by demonstrating that temporal variation in foraging consistency within populations leads to different fitness pay‐offs. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.